High-activity self-repairing anti-permeability phosphogypsum filling solidifying agent and preparation and application thereof

Through the synergistic effect of the inorganic matrix and functional modified components of the highly active self-healing and impermeable phosphogypsum filling curing agent, the problems of incomplete hydration reaction, low early strength and poor impermeability of the phosphogypsum filling system are solved. It achieves high hydration reaction degree, early strength and crack self-healing effect for underground mine filling, and is suitable for underground mine filling, water-bearing goaf backfilling and water-rush roadway filling projects.

CN122789685BActive Publication Date: 2026-11-06SICHUAN INSITITUTE OF BUILDING RES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611231077.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-11-06
Estimated Expiration
2046-08-14

AI Technical Summary

Technical Problem

Existing phosphogypsum filling and curing systems suffer from incomplete hydration reaction, low early strength, loose matrix, poor impermeability, water seepage failure after cracking, insufficient water immersion stability, and lack of self-healing ability, making it difficult to meet the engineering requirements of complex, highly disturbed water-bearing environments in underground mines.

Method used

The high-activity self-healing and impermeable phosphogypsum filling and curing agent is composed of inorganic matrix components and functional modification components, including pretreated carbide slag powder, limestone powder, steel slag, silicate cement clinker powder, slag powder, silica fume, lithium slag powder, modified lignin sulfonate powder, sodium carboxymethyl cellulose powder, and gypsum penetrating crystallization self-healing powder. Through synergistic effects, it achieves high hydration reactivity, early strength, density, and crack self-healing function.

Benefits of technology

It significantly improves the degree of hydration reaction and early strength, enables self-repair of cracks larger than 0.5mm, achieves a permeability grade of P12, has a permeability pressure of not less than 1.2MPa, and reduces the chloride ion diffusion coefficient by more than 30%, making it suitable for underground filling construction in mines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122789685B_ABST
    Figure CN122789685B_ABST
Patent Text Reader

Abstract

This invention relates to the field of building materials technology, specifically disclosing a highly active self-healing and impermeable phosphogypsum filling curing agent and its preparation and application. The curing agent consists of 100 parts of an inorganic matrix component and 3-7 parts of a functional modification component. The inorganic matrix component includes: pretreated carbide slag powder, limestone powder, steel slag, and highly active slag powder; the functional modification component includes: modified lignin sulfonate powder, sodium carboxymethyl cellulose powder, and gypsum penetrating crystallization self-healing powder. The preparation method of this curing agent and its application in mine backfilling are also disclosed. Its advantages are: 1) Through alkaline pretreatment with highly active slag and phosphogypsum containing ≥80% Q1+Q2 content, the degree of hydration reaction and early strength are significantly improved; 2) The ternary penetrating crystallization components work synergistically to achieve a multi-level crystallization self-healing mechanism, which can repair cracks with a width of ≥0.5mm; 3) The impermeability grade is ≥P12, and the secondary permeability grade ratio can reach ≥1.6, with comprehensive performance significantly superior to existing technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of self-healing waterproof building materials technology, specifically to a highly active self-healing and impermeable phosphogypsum filling and curing agent, its preparation and application. Background Technology

[0002] Phosphogypsum is a large-scale industrial solid waste generated during the production of phosphate fertilizer. Its stockpiles are huge and its comprehensive utilization rate is low. Long-term open-air stockpiling can easily lead to environmental problems such as soil salinization and excessive phosphorus and fluoride in groundwater. Utilizing phosphogypsum to prepare mine filling solidification agents is an important way to achieve its large-scale, harmless and resource-based utilization.

[0003] Traditional phosphogypsum filling and solidification systems often employ pure inorganic compound schemes of slag, steel slag, and quicklime, which have significant technical shortcomings: First, the surface of phosphogypsum is covered with a large amount of soluble phosphorus and hydrofluoric acid impurities, which significantly inhibit the hydration reaction of the cementitious components and reduce the overall hydration reaction degree of the system; Second, ordinary commercial granulated blast furnace slag has a high degree of glassy polymerization, with a large proportion of low-activity Q3 and Q4 structures, resulting in insufficient dissolution of effective active components, slow generation rate of hydration products, and low conversion rate; Third, pure inorganic hydration systems have high packing porosity and well-developed interconnected pores, resulting in poor matrix compactness, making it difficult to achieve early strength standards, and also causing prominent problems of water bleeding and slurry penetration.

[0004] Mine backfill is highly susceptible to microcracks and minute through-cracks due to ground pressure disturbance, wet-dry cycles, and temperature changes. Ordinary modification systems lack the ability to actively repair cracks; once cracks appear, the waterproofing structure fails directly, allowing water to rapidly penetrate along the cracks. This causes the backfill to soften, crumble, and experience long-term strength loss, leading to water seepage and grout leakage in the tunnels, resulting in a significant decrease in service durability. Single activation or single hydrophobic modification schemes cannot simultaneously achieve the comprehensive effects of "easy dry powder application, high early strength, low initial permeability, self-healing cracks, and long-term water resistance and durability," making it difficult to meet the engineering requirements of complex, water-bearing, and highly disturbed underground backfilling.

[0005] Several improvement solutions have been proposed. For example, Chinese patent CN120682009A discloses a phosphogypsum-based high-strength impermeable filling material that fills microcracks by introducing electrolytic manganese slag to generate manganese alum crystals. However, this system relies on electrolytic manganese slag containing pollutants such as chromium, posing environmental risks. Chinese patent CN113060961A discloses an activator for mine filling materials and its preparation method, using steel slag as raw material and adding superabsorbent polymer and microcrystalline cellulose for alkali activation. However, this system lacks crack self-healing function. Chinese patent CN119751012A discloses a low-alkalinity, early-strength phosphogypsum filling and curing material, using inorganic compounds such as silica fume, limestone powder, slag powder, and metakaolin, which also does not involve crystallization self-healing function. Therefore, there is an urgent need to develop a composite curing agent system that is all-dry powder, easy to industrialize, compatible with pretreated phosphogypsum, has high hydration reactivity, high density, and combines penetrating crystallization water-blocking and crack self-healing functions. Summary of the Invention

[0006] To address the problems existing in the prior art, such as incomplete hydration reaction, low early strength, loose matrix, poor impermeability, water seepage failure after cracking, insufficient water immersion stability, lack of self-healing ability, and poor workability of liquid additives, this invention provides a highly active self-healing impermeable phosphogypsum filling and curing agent, as well as its preparation and application.

[0007] To address the aforementioned technical problems, this invention, through in-depth research and process optimization, proposes the following technical solution:

[0008] A highly active self-healing and impermeable phosphogypsum filling and curing agent is composed of the following components in the indicated mass proportions: 100 parts inorganic matrix component and 3-7 parts functional modification component; the inorganic matrix component includes the following components in the indicated mass proportions: 1-3 parts pretreated calcium carbide slag powder, 4-6 parts limestone powder, 12-17 parts steel slag, 15-25 parts silicate cement clinker powder, 20-30 parts slag powder, 3-8 parts silica fume, and 10-20 parts lithium slag powder; the functional modification component includes the following components in the indicated mass proportions: 0.4-0.6 parts modified lignin sulfonate powder, 0.1-0.3 parts sodium carboxymethyl cellulose powder, and 4-5 parts gypsum penetrating crystallization self-healing powder; wherein the gypsum penetrating crystallization self-healing powder contains a penetrating crystallization component, which is composed of sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals in a ratio of 1.2-2.5: Composition in a mass ratio of 0.8~2.0 : 0.4~1.0.

[0009] In the inorganic matrix components, pretreated calcium carbide slag powder (calcium carbide slag powder after drying and grinding, with calcium hydroxide as its main component) acts as an alkaline activator, providing OH⁻, disrupting the glassy structure of the mineral admixtures, activating the hydration reaction, and neutralizing acidic impurities in phosphogypsum. Limestone powder acts as a micro-aggregate filler, physically filling pores, improving particle size distribution, reducing capillary porosity, and increasing density. Steel slag acts as an auxiliary cementitious material, containing a small amount of free CaO and active silicates, assisting in providing an alkaline environment and cementitious components, promoting the formation of hydration products, and compensating for shrinkage through its micro-expansion properties. Silicate cement clinker powder, slag powder, silica fume, and lithium slag powder are the core cementitious materials, providing active silicon and aluminum ions, which, under alkaline activation, generate hydration gels such as CSH and CAH, determining the strength and density of the solidified body.

[0010] As will be readily understood by those skilled in the art, in this invention, the steel slag refers to a grayish-black powder produced by processing molten slag discharged during the steelmaking process in converters, electric furnaces, or open-hearth furnaces through cooling, crushing, magnetic separation, and grinding. Its chemical composition is primarily composed of calcium oxide (CaO, 35%–50%), iron oxide (Fe2O3, 15%–30%), and silicon dioxide (SiO2, 12%–25%), with some magnesium oxide (MgO, 3%–8%) and aluminum oxide (Al2O3, approximately 2%–6%). The mineral composition of steel slag is similar to that of silicate cement clinker, mainly containing cementing minerals with potential hydraulic activity such as tricalcium silicate (C3S), dicalcium silicate (C2S), and calcium ferrite, as well as small amounts of free calcium oxide (f-CaO, typically controlled at ≤4.0%), periclase (MgO), and RO phase (CaO-FeO-MgO-MnO solid solution).

[0011] As will be readily understood by those skilled in the art, in this invention, the silicate cement clinker powder refers to clinker made primarily from limestone and clay, calcined at high temperatures, and composed mainly of tricalcium silicate (C3S), dicalcium silicate (C2S), tricalcium aluminate (C3A), and tetracalcium aluminoferrite (C4AF), which is then ground into powder. The slag powder refers to glassy powder with potential hydraulic properties, obtained by water quenching and grinding molten slag produced in blast furnace ironmaking. The silica fume refers to ultrafine powder obtained by collecting the dust generated during the smelting of ferrosilicon or industrial silicon. The lithium slag powder refers to powder obtained by drying and grinding the waste residue generated during lithium salt production. All of the above materials possess potential hydraulic properties or pozzolanic activity and can be used alone or in combination. This invention preferably uses the four materials in a specific ratio to achieve a synergistic and complementary effect.

[0012] In this invention, the nano-hydrated calcium silicate seed crystals (nano-CSH) refer to synthetic hydrated calcium silicate crystals with a particle size of 20-50 nm. They are typically prepared by a precipitation reaction of sodium silicate solution and calcium nitrate solution in the presence of a dispersant. This preparation can be done by those skilled in the art or purchased directly from the market. Alternatively, commercially available nano-CSH seed crystal suspensions can be spray-dried to obtain powder. These seed crystals serve as heterogeneous nucleation sites, inducing free calcium and silicate ions to crystallize directionally on their surface, forming a dense CSH gel phase.

[0013] In the functional modification components, modified lignin sulfonate powder acts as a water-reducing agent / dispersant, lowering the slurry yield stress, improving fluidity, reducing mixing water consumption, and improving workability. Sodium carboxymethyl cellulose powder acts as a thickening and water-retaining agent, increasing slurry viscosity, preventing bleeding, segregation, and slurry penetration, and ensuring the uniformity of the filling slurry during transportation and casting.

[0014] The gypsum-penetrating crystallizing self-healing powder contains a penetrating crystallizing component composed of sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals. This penetrating crystallizing component, when placed in the alkaline environment of the phosphogypsum filler, can respond to water seepage from cracks by triggering a multi-level crystallization reaction: through hydrolysis releasing active ions, inducing directional recrystallization, and providing heterogeneous nucleation sites, it generates multiple low-solubility crystalline phases such as calcium fluorosilicate, calcium phosphate, and CSH gel layer by layer in the crack region, forming a multi-layered crystalline self-healing network from initial rapid sealing to gradual dense filling, and then to uniform growth guided by crystal nuclei. The synergistic self-healing mechanism formed by the three components can effectively and autonomously repair cracks with a width of 0.5 mm or more.

[0015] As a further improvement of the present invention, the slag powder satisfies the following microstructure parameters: slag quality coefficient ≥ 1.4, and based on² 9 Si NMR microstructure characterization revealed that the total relative content of low-polymerization-degree active structures Q1+Q2 in the slag glass was ≥80%, while the total content of high-polymerization-degree inert structures Q3+Q4 was ≤20%. This scheme specifically defines the activity indicators of the slag. It will be readily understood by those skilled in the art that Q1, Q2, Q3, and Q4 are based on² 9The degree of polymerization of silicon-oxygen tetrahedra in the Si NMR spectrum classifies the structural units of silicate glass as follows: Q0 represents isolated silicon-oxygen tetrahedra (no bridging oxygen), Q1 represents end-group silicon-oxygen tetrahedra (one bridging oxygen), Q2 represents in-chain silicon-oxygen tetrahedra (two bridging oxygen), Q3 represents layered or plate-like silicon-oxygen tetrahedra (three bridging oxygen), and Q4 represents three-dimensional network silicon-oxygen tetrahedra (four bridging oxygen). Q1 and Q2 are low-polymerization structures with low bond energies and high non-bridging oxygen content, making them prone to depolymerization and breakage under alkaline excitation conditions, rapidly releasing active silicon and aluminum ions to participate in the hydration reaction. Q3 and Q4 are high-polymerization inert structures with high bond energies and stable structures, making them difficult to be destroyed by alkaline exciters and exhibiting low hydration activity. This invention ensures high reactivity of the slag by controlling the total relative content of Q1+Q2 to ≥80% and the total content of Q3+Q4 to ≤20%, thereby guaranteeing the early strength development and hydration reaction degree of the solidified body. If the Q1+Q2 content is less than 80%, the proportion of inert Q3+Q4 structure in the slag is relatively high, the hydration conversion rate decreases, and the early strength development is insufficient.

[0016] As a further improvement of the present invention, the gypsum penetrating crystallization self-healing powder is composed of the following components in the following mass proportions: 2.5-5 parts penetrating crystallization component, 0.2-0.5 parts surface vapor-precipitated waterproof powder, 0.2-0.8 parts nano-silica, and 0.04-0.25 parts auxiliary crystal growth regulating component. This scheme specifically defines the auxiliary components of the gypsum penetrating crystallization self-healing powder. The surface vapor-precipitated waterproof powder is an organosilicon hydrophobic powder, whose active silyl groups are chemically bonded to the hydroxyl groups in cement hydration products, forming a hydrophobic network on the inner wall of the pores, significantly reducing capillary water absorption. Nano-silica fills nanoscale pores, refines the pore structure, and simultaneously acts as a heterogeneous nucleation point to promote uniform growth of the crystalline phase. The auxiliary crystal growth regulating component is used to moderately complex calcium ions, regulate the crystallization reaction rate, avoid premature and rapid consumption of crystals, and achieve controllable timing and long-term release of the crystallization reaction.

[0017] As a further improvement of the present invention, the auxiliary crystal growth regulating component is composed of sodium citrate and sodium gluconate in a mass ratio of 1:0.8 to 1.4. Within this ratio range, the two regulators can produce a synergistic complexing effect, effectively controlling the crystallization rate and making the crack self-healing process smoother and more durable.

[0018] As a further improvement of the present invention, the modified lignin sulfonate powder is prepared by sulfonation modification of calcium lignin sulfonate or sodium lignin sulfonate. Technicians can directly purchase modified lignin sulfonate powder that meets the water reduction rate requirements (e.g., water reduction rate ≥ 15%) from the market, or prepare it themselves using conventional sulfonation modification methods. The surface vapor-phase precipitated waterproof powder is an organosilicon alkyl hydrophobic powder, which can be purchased directly from the market, such as SILRES® POWDER A or TEGO® Protect series products.

[0019] This invention also discloses a method for preparing the above-mentioned highly active self-healing and impermeable phosphogypsum filling and curing agent, comprising the following steps:

[0020] A. Weigh each raw material of the inorganic matrix component and the functional modification component according to the formula;

[0021] B. Add the pretreated carbide slag powder, limestone powder, steel slag, silicate cement clinker powder, slag powder, silica fume, and lithium slag powder from the inorganic matrix components into a dry powder mixer and stir at a speed of 500-800 r / min for 3-5 min to obtain inorganic mixed powder.

[0022] C. Add the modified lignin sulfonate powder, sodium carboxymethyl cellulose powder, and gypsum penetrating crystallization self-healing powder from the functional modification components to the inorganic mixed powder obtained in step B, and continue stirring at a speed of 800-1000 r / min for 5-8 min until all components are mixed evenly and there is no segregation, to obtain a highly active self-healing anti-permeability phosphogypsum filling and curing agent.

[0023] This preparation method uses a dry powder mixing process, in which all components are powders, requiring no liquid additives. It is simple to operate, mixes evenly, and the resulting curing agent can be stored for a long time and transported in bags, making it suitable for large-scale industrial production.

[0024] As a further improvement to the preparation method of this invention, the gypsum penetrating crystallization self-healing powder in step C is prepared as follows: Sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals are weighed according to the specified ratio, and then added together with nano-silica, surface vapor-precipitated waterproof powder, and auxiliary crystal growth regulating components into a mixer. The mixture is stirred at a speed of 1000-1500 r / min for 3-5 min to obtain the gypsum penetrating crystallization self-healing powder for later use. This scheme, through pre-mixing treatment, ensures that the components of the penetrating crystallization are uniformly dispersed, so that sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals reach a molecular-level mixed state in the powder, which is beneficial to the uniform distribution and synergistic effect in the subsequent filling body.

[0025] This invention also discloses a method for preparing filling slurry using the above-mentioned highly active self-healing and impermeable phosphogypsum filling and curing agent, comprising the following steps:

[0026] S1. Pretreatment of dihydrate phosphogypsum: Add 0.5% to 1% of its own weight of quicklime to dihydrate phosphogypsum, mix thoroughly and uniformly, and then let it stand at room temperature in a sealed environment for 20 to 30 hours to obtain pretreated phosphogypsum.

[0027] S2. Weigh out the high-activity self-healing anti-seepage phosphogypsum filling and curing agent, the pretreated phosphogypsum and water in a mass ratio of 1:5~7:12~16;

[0028] S3. Add the highly active self-healing and impermeable phosphogypsum filling and curing agent and the pretreated phosphogypsum into the mixer and dry mix for 30-60 seconds.

[0029] S4. Add clean water and mix for 3-5 minutes at a speed of 60-100 r / min until the slurry is uniform, free of agglomerates and lumps, and has stable fluidity to obtain the filling slurry;

[0030] The filling grout is poured into shape and cured at room temperature with standard moisture retention.

[0031] In step S1, the pretreatment of dihydrate phosphogypsum is one of the key steps. Adding 0.5% to 1% quicklime to the dihydrate phosphogypsum and allowing it to stand at room temperature in a sealed environment for 20 to 30 hours can effectively neutralize acidic inhibitory impurities such as free phosphoric acid and soluble fluorides in the phosphogypsum, eliminating the toxic effects of these impurities on the gelation and hydration reaction. At the same time, trace amounts of dihydrate gypsum crystal nuclei are generated in situ, providing sufficient heterogeneous nucleation sites for subsequent hydration reactions and effectively accelerating the precipitation and accumulation of hydration products.

[0032] In step S2, the mass ratio of curing agent: pretreated phosphogypsum: water is 1:6:14. This is the optimal ratio obtained by the inventors through extensive experimentation. Under this ratio, the slurry has suitable fluidity and workability, and the cured body can obtain optimal mechanical properties and impermeability.

[0033] This invention also discloses the application of the above-mentioned highly active self-healing and impermeable phosphogypsum filling and curing agent or the above-mentioned filling slurry in underground mine filling, water-bearing goaf backfilling, water-bearing roadway and wet stratum filling projects.

[0034] Compared with the prior art, the beneficial effects of the present invention are:

[0035] 1) This invention significantly improves the degree of hydration reaction and early strength by using highly active slag powder (Q1+Q2 content ≥80%) as the core cementitious component, combined with the multi-component composite synergistic effect of silicate cement clinker powder, silica fume, and lithium slag powder, as well as the alkaline pretreatment process of phosphogypsum. The 3-day compressive strength is ≥2.5MPa, the 5-day compressive strength is ≥4.0MPa, and the 28-day compressive strength is ≥9.0MPa.

[0036] 2) This invention constructs a ternary permeable crystallization component composed of sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals in a specific ratio. The three components work synergistically to achieve a multi-level crystallization self-healing mechanism, which can repair cracks with a width of 0.5 mm or more. With the assistance of nano-silica to fill the pores, waterproof powder to form a hydrophobic network, and crystallization regulator to control the repair reaction sequence, the overall impermeability grade is ≥P12 (i.e., impermeability pressure is not less than 1.2 MPa, corresponding to a reduction of chloride ion diffusion coefficient of more than 30%), and the secondary permeability grade ratio can reach more than 1.6.

[0037] 3) This invention uses a completely dry powder formula, all components are dry powder, no liquid additives are required, it can be stored for a long time and transported in bags, the slurry has stable fluidity and no bleeding or seepage, and it is suitable for underground filling construction conditions in mines. Attached Figure Description

[0038] Figure 1 This is a process flow diagram of Embodiment 1 of the specific implementation method. Detailed Implementation

[0039] To enable those skilled in the art to better implement the present invention, the present invention will be further described below with reference to embodiments. However, it should be understood that the present invention is not limited to the following embodiments.

[0040] For ease of comparison, the raw materials used in the following examples and comparative examples are all from the same batch, and the specific parameters of the raw materials are as follows:

[0041] Pretreated calcium carbide slag powder: Industrial grade, dried and ground, with Ca(OH)2 content ≥85% and fineness 200 mesh, obtained by pretreatment of commercially available calcium carbide slag;

[0042] Limestone powder: Industrial grade, CaCO3 content ≥95%, fineness 200 mesh, commercially available;

[0043] Steel slag: Industrial grade, specific surface area ≥400m² / kg, free CaO content ≤3%, commercially available;

[0044] Silicate cement clinker powder: industrial grade, specific surface area ≥350m² / kg, conforming to the requirements of GB / T 21372-2008 "Silicate Cement Clinker", commercially available;

[0045] Slag powder: quality coefficient ≥ 1.4,² 9 Si NMR characterization showed a total relative content of 83% for Q1+Q2 and 17% for Q3+Q4, with a specific surface area of ​​510 m² / kg. It is commercially available.

[0046] Silica fume: Industrial grade, SiO2 content ≥92%, specific surface area ≥15000m² / kg, commercially available;

[0047] Lithium slag powder: industrial grade, specific surface area ≥400m² / kg, commercially available;

[0048] Dihydrate phosphogypsum: an industrial by-product, with calcium sulfate dihydrate content ≥85%, free water content ≤15%, pH=2~4, commercially available;

[0049] Modified lignin sulfonate powder: Sodium lignin sulfonate is sulfonated and modified, with a water reduction rate of ≥15%, commercially available;

[0050] Sodium carboxymethyl cellulose (CMC) powder: industrial grade, viscosity ≥600 mPa·s (2% aqueous solution, 25℃), commercially available;

[0051] Sodium fluorosilicate (Na2SiF6): Industrial grade, purity ≥98%, fineness 200 mesh, commercially available;

[0052] Hydroxyapatite (Ca5(PO4)3(OH)): Industrial grade, purity ≥95%, fineness 300 mesh, commercially available;

[0053] Nano-hydrated calcium silicate seed crystals (nano-CSH): Industrial grade, particle size 20-50nm, solid content ≥20%, commercially available;

[0054] Nano-SiO2: Industrial grade, particle size 10-20nm, purity ≥99.5%, commercially available;

[0055] Waterproof powder for surface vapor deposition: Organosilicon alkyl hydrophobic powder, model SILRES® POWDER A, Wacker Chemie;

[0056] Sodium citrate: analytical grade, purity ≥99%, commercially available;

[0057] Sodium gluconate: analytical grade, purity ≥98%, commercially available;

[0058] Clear water: municipal tap water.

[0059] Unless otherwise specified, the gypsum penetrating crystallization self-healing powder used in the following examples and comparative examples was prepared according to the following premixing method: sodium fluorosilicate, hydroxyapatite, nano-hydrated calcium silicate seed crystals, nano-silica, surface vapor-precipitated waterproof powder, sodium citrate and sodium gluconate were weighed according to the ratio and put into a small high-speed mixer. The mixture was stirred at 1200 r / min for 4 min to obtain the gypsum penetrating crystallization self-healing powder for later use.

[0060] Example 1:

[0061] A highly active self-healing and impermeable phosphogypsum filling and curing agent was prepared according to the following method:

[0062] S1. Weigh the following raw materials for the inorganic matrix components according to the following mass proportions: 2 parts of pretreated calcium carbide slag powder, 5 parts of limestone powder, 16 parts of steel slag, 22 parts of silicate cement clinker powder, 30 parts of slag powder, 7 parts of silica fume, and 18 parts of lithium slag powder.

[0063] S2. Weigh the raw materials of the functional modification components according to the following mass proportions: 0.5 parts of modified lignin sulfonate powder, 0.2 parts of sodium carboxymethyl cellulose powder, and 4.5 parts of gypsum penetrating crystallization self-healing powder.

[0064] The gypsum penetrating crystallization self-repairing powder is prepared as follows: 1.6 parts of sodium fluorosilicate, 1.4 parts of hydroxyapatite, 0.8 parts of nano-hydrated calcium silicate seed crystals (total of penetrating crystallization components: 3.8 parts), 0.4 parts of nano-silica, 0.2 parts of surface vapor-precipitated waterproof powder, 0.05 parts of sodium citrate, and 0.05 parts of sodium gluconate are added together into a small high-speed mixer and stirred at 1200 r / min for 4 min to obtain the gypsum penetrating crystallization self-repairing powder.

[0065] S3. Add the inorganic matrix components weighed in step S1 into a dry powder mixer and stir at a speed of 650 r / min for 4 min to obtain inorganic mixed powder.

[0066] S4. Add the raw materials of the functional modification components (modified lignin sulfonate powder, sodium carboxymethyl cellulose powder and the above-mentioned gypsum penetrating crystallization self-healing powder) weighed in step S2 to the inorganic mixed powder obtained in step S3, and continue to stir at a speed of 900 r / min for 6 min until the components are mixed evenly and there is no segregation, to obtain a highly active self-healing anti-permeability phosphogypsum filling curing agent, which is denoted as curing agent A.

[0067] Example 2:

[0068] A highly active self-healing and impermeable phosphogypsum filling and curing agent was prepared according to the following method:

[0069] S1. Weigh the following raw materials for the inorganic matrix components according to the following mass proportions: 1 part of pretreated calcium carbide slag powder, 5 parts of limestone powder, 16 parts of steel slag, 24 parts of silicate cement clinker powder, 30 parts of slag powder, 6 parts of silica fume, and 18 parts of lithium slag powder.

[0070] S2. Weigh the raw materials of the functional modification components according to the following mass proportions: 0.4 parts of modified lignin sulfonate powder, 0.1 parts of sodium carboxymethyl cellulose powder, and 4.0 parts of gypsum penetrating crystallization self-healing powder.

[0071] The gypsum penetrating crystallization self-repairing powder is prepared as follows: 1.2 parts of sodium fluorosilicate, 1.0 part of hydroxyapatite, 0.6 parts of nano-hydrated calcium silicate seed crystals (total of penetrating crystallization components: 2.8 parts), 0.6 parts of nano-silica, 0.4 parts of surface vapor-precipitated waterproof powder, 0.1 parts of sodium citrate, and 0.1 parts of sodium gluconate are added together into a small high-speed mixer and stirred at 1000 r / min for 5 min to obtain the gypsum penetrating crystallization self-repairing powder.

[0072] S3. Add the inorganic matrix components weighed in step S1 into a dry powder mixer and stir at 500 r / min for 3 min to obtain inorganic mixed powder.

[0073] S4. Add the raw materials of the functional modification components (modified lignin sulfonate powder, sodium carboxymethyl cellulose powder and the above-mentioned gypsum penetrating crystallization self-healing powder) weighed in step S2 to the inorganic mixed powder obtained in step S3, and continue to stir at a speed of 800 r / min for 5 min until the components are mixed evenly and there is no segregation, to obtain a highly active self-healing anti-permeability phosphogypsum filling curing agent, which is denoted as curing agent B.

[0074] Example 3:

[0075] A highly active self-healing and impermeable phosphogypsum filling and curing agent was prepared according to the following method:

[0076] S1. Weigh the following raw materials for the inorganic matrix components according to the following mass proportions: 3 parts of pretreated calcium carbide slag powder, 6 parts of limestone powder, 17 parts of steel slag, 24 parts of silicate cement clinker powder, 28 parts of slag powder, 8 parts of silica fume, and 14 parts of lithium slag powder.

[0077] S2. Weigh the raw materials of the functional modification components according to the following mass proportions: 0.6 parts of modified lignin sulfonate powder, 0.3 parts of sodium carboxymethyl cellulose powder, and 5.0 parts of gypsum penetrating crystallization self-healing powder.

[0078] The gypsum penetrating crystallization self-repairing powder is prepared as follows: 1.6 parts of sodium fluorosilicate, 1.4 parts of hydroxyapatite, 0.8 parts of nano-hydrated calcium silicate seed crystals (total of penetrating crystallization components: 3.8 parts), 0.6 parts of nano-silica, 0.4 parts of surface vapor-precipitated waterproof powder, 0.1 parts of sodium citrate, and 0.1 parts of sodium gluconate are added together into a small high-speed mixer and stirred at 1500 r / min for 3 min to obtain the gypsum penetrating crystallization self-repairing powder.

[0079] S3. Add the inorganic matrix components weighed in step S1 into a dry powder mixer and stir at 800 r / min for 5 min to obtain inorganic mixed powder.

[0080] S4. Add the raw materials of the functional modification components (modified lignin sulfonate powder, sodium carboxymethyl cellulose powder and the above-mentioned gypsum penetrating crystallization self-healing powder) weighed in step S2 to the inorganic mixed powder obtained in step S3, and continue to stir at a speed of 1000 r / min for 8 min until the components are mixed evenly and there is no segregation, to obtain a highly active self-healing anti-permeability phosphogypsum filling curing agent, which is denoted as curing agent C.

[0081] Comparative Example 1 (containing only hydroxyapatite and nano-CSH seeds, without sodium fluorosilicate)

[0082] This comparative example serves as a control experiment for Example 1, conducted according to the same steps as Example 1, with the difference being that sodium fluorosilicate is not added to the gypsum penetrating crystallization self-healing powder. The penetrating crystallization component consists only of hydroxyapatite and nano-hydrated calcium silicate seed crystals, and the total amount of both is the same as that of the penetrating crystallization component in Example 1 (3.8 parts), while the ratio remains the same as in Example 1 (hydroxyapatite: nano-hydrated calcium silicate seed crystals = 1.4:0.8 = 1.75:1). The specific scheme is as follows:

[0083] S1, Same as Example 1.

[0084] S2, same as Example 1.

[0085] The composition of the gypsum penetrating crystallization self-healing powder is as follows: 2.418 parts hydroxyapatite, 1.382 parts nano-hydrated calcium silicate seed crystals (total 3.8 parts), 0.4 parts nano-silica, 0.2 parts surface vapor-precipitated waterproof powder, and 0.1 parts auxiliary crystal growth regulating component (sodium citrate:sodium gluconate = 1:1). The total amount of the above components is 4.5 parts.

[0086] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is referred to as the comparative curing agent D1.

[0087] Comparative Example 2 (containing only sodium fluorosilicate and nano-CSH seeds, without hydroxyapatite)

[0088] This comparative example serves as a control experiment for Example 1, conducted according to the same steps as Example 1, with the difference being that hydroxyapatite is not added to the gypsum penetrating crystallization self-healing powder. The penetrating crystallization component consists only of sodium fluorosilicate and nano-hydrated calcium silicate seed crystals, and the total amount of both is the same as the total amount of the penetrating crystallization component in Example 1 (3.8 parts), while the ratio of the two remains the same as in Example 1 (sodium fluorosilicate: nano-hydrated calcium silicate seed crystals = 1.6:0.8 = 2:1). The specific scheme is as follows:

[0089] S1, Same as Example 1.

[0090] S2, same as Example 1.

[0091] The composition of the gypsum penetrating crystallization self-healing powder is as follows: 2.533 parts sodium fluorosilicate, 1.267 parts nano-hydrated calcium silicate seed crystals (total 3.8 parts), 0.4 parts nano-silica, 0.2 parts surface vapor-precipitated waterproof powder, and 0.1 parts auxiliary crystal growth regulating component (sodium citrate:sodium gluconate = 1:1). The total amount of the above components is 4.5 parts.

[0092] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is designated as comparative curing agent D2.

[0093] Comparative Example 3 (without nano-CSH seed crystals, containing only sodium fluorosilicate and hydroxyapatite)

[0094] This comparative example serves as a control experiment for Example 1, conducted according to the same steps as Example 1, with the difference being that: no nano-hydrated calcium silicate seed crystals are added to the gypsum penetrating crystallization self-healing powder; the penetrating crystallization component consists only of sodium fluorosilicate and hydroxyapatite, and the total amount of both is the same as the total amount of the penetrating crystallization component in Example 1 (3.8 parts), and the ratio of the two remains the same as in Example 1 (sodium fluorosilicate:hydroxyapatite = 1.6:1.4 = 8:7 ≈ 1.1429:1). The specific scheme is as follows:

[0095] S1, Same as Example 1.

[0096] S2, same as Example 1.

[0097] The composition of the gypsum penetrating crystallization self-healing powder is as follows: sodium fluorosilicate 2.027 parts, hydroxyapatite 1.773 parts (total 3.8 parts), nano silica 0.4 parts, surface vapor-precipitated waterproof powder 0.2 parts, and auxiliary crystal growth regulating component (sodium citrate:sodium gluconate = 1:1) 0.1 parts. The total amount of the above components is 4.5 parts.

[0098] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is referred to as the comparative curing agent D3.

[0099] Comparative Example 4 (containing only sodium fluorosilicate)

[0100] This comparative example is a control experiment of Example 1, conducted according to the same steps as Example 1, with the difference that only sodium fluorosilicate is added as a single penetrating crystallization component to the gypsum penetrating crystallization self-healing powder, with a mass fraction of 3.8 parts, and it does not contain hydroxyapatite or nano-hydrated calcium silicate seed crystals. The specific scheme is as follows:

[0101] S1, Same as Example 1.

[0102] S2, same as Example 1.

[0103] The composition of the gypsum penetrating crystallization self-healing powder is as follows: 3.8 parts sodium fluorosilicate, 0.4 parts nano silica, 0.2 parts surface vapor-precipitated waterproof powder, and 0.1 parts auxiliary crystal growth regulating component (sodium citrate:sodium gluconate = 1:1). The total amount of the above components is 4.5 parts.

[0104] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is designated as comparative curing agent D4.

[0105] Comparative Example 5 (containing only hydroxyapatite as a single component)

[0106] This comparative example is a control experiment of Example 1, conducted according to the same steps as Example 1, with the difference being that only hydroxyapatite was added as a single penetrating crystallization component to the gypsum penetrating crystallization self-healing powder, with a mass fraction of 3.8 parts, and it did not contain sodium fluorosilicate or nano-hydrated calcium silicate seed crystals. The specific scheme is as follows:

[0107] S1, Same as Example 1.

[0108] S2, same as Example 1.

[0109] The composition of the gypsum penetrating crystallization self-healing powder is as follows: 3.8 parts hydroxyapatite, 0.4 parts nano silica, 0.2 parts surface vapor-precipitated waterproof powder, and 0.1 parts auxiliary crystal growth regulating component (sodium citrate:sodium gluconate = 1:1). The total amount of the above components is 4.5 parts.

[0110] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is designated as comparative curing agent D5.

[0111] Comparative Example 6 (containing only a single component: nano-hydrated calcium silicate seed crystals)

[0112] This comparative example is a control experiment of Example 1, conducted according to the same steps as Example 1, with the difference that only nano-hydrated calcium silicate seed crystals were added as a single penetrating crystallization component to the gypsum penetrating crystallization self-healing powder, with a mass fraction of 3.8 parts, and it does not contain sodium fluorosilicate or hydroxyapatite. The specific scheme is as follows:

[0113] S1, Same as Example 1.

[0114] S2, same as Example 1.

[0115] The composition of the gypsum penetrating crystallization self-healing powder is as follows: 3.8 parts of nano-hydrated calcium silicate seed crystals, 0.4 parts of nano-silica, 0.2 parts of surface vapor-precipitated waterproof powder, and 0.1 parts of auxiliary crystal growth regulating component (sodium citrate:sodium gluconate = 1:1). The total amount of the above components is 4.5 parts.

[0116] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is designated as comparative curing agent D6.

[0117] Comparative Example 7 (excluding auxiliary components, containing only ternary permeation crystallization components)

[0118] This comparative example serves as a control experiment for Example 1, conducted according to the same steps as Example 1, with the difference being that the gypsum penetrating crystallization self-healing powder does not contain nano-silica, surface vapor-precipitated waterproof powder, or auxiliary crystal growth regulating components. Only the ternary penetrating crystallization components (sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals) are retained, with the total amount being the same as in Example 1 (3.8 parts), and the ratio being the same as in Example 1 (1.6:1.4:0.8). To maintain the total mass fraction of the gypsum penetrating crystallization self-healing powder consistent with Example 1 (4.5 parts), an additional 0.7 parts of inert filler (finely ground limestone powder, 200 mesh) are added. The specific scheme is as follows:

[0119] S1, Same as Example 1.

[0120] S2, same as Example 1.

[0121] The composition of the gypsum penetrating crystallization self-healing powder is as follows: sodium fluorosilicate 1.6 parts, hydroxyapatite 1.4 parts, nano-hydrated calcium silicate seed crystals 0.8 parts (total of ternary components 3.8 parts), and inert filler (limestone powder) 0.7 parts. The total amount of the above components is 4.5 parts.

[0122] S3 to S4 are the same as in Example 1. The highly active self-healing and impermeable phosphogypsum filling and curing agent prepared is designated as comparative curing agent D7.

[0123] Pretreatment of phosphogypsum:

[0124] In the following examples and comparative examples, the pretreated phosphogypsum required for filling slurry preparation was prepared according to the following method: 0.8% of its own mass of quicklime was added to dihydrate phosphogypsum, and after thorough mixing, it was left to stand at room temperature for 24 hours to obtain pretreated phosphogypsum.

[0125] Preparation of filling slurry

[0126] The curing agents A, B, and C, as well as the comparative curing agents D1 to D7, were used to prepare the filling slurry. The specific steps are as follows:

[0127] S1. Weigh out the curing agent, the above-pretreated phosphogypsum and water in a mass ratio of 1:6:14.

[0128] S2. Add the curing agent and pretreated phosphogypsum into the mixer and dry mix for 45 seconds.

[0129] S3. Add clean water and mix at 80 r / min for 4 minutes until the slurry is uniform, free of agglomerates and lumps, and has stable fluidity to obtain the filling slurry.

[0130] The filling slurries prepared above are respectively designated as slurry A, slurry B, slurry C, and control slurries D1 to D7, corresponding to different curing agents.

[0131] Performance verification experiment:

[0132] The above-mentioned grouts A, B, and C, as well as the control grouts D1 to D7, were cast into standard specimens (cured under the same conditions at room temperature with standard moisture retention), and their performance was tested according to relevant standards. Compressive strength testing was conducted according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)," and water permeability testing was conducted according to the water permeability test method in GB / T 50082-2009 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete."

[0133] (a) Mechanical property testing

[0134] Each grout was cast into 70.7mm×70.7mm×70.7mm cubic specimens and cured for 3 days, 5 days, and 28 days under standard curing conditions of 20±2℃ and relative humidity above 95%. The compressive strength at each age was then determined. Six specimens were taken from each test group, and the average value was calculated. The results are shown in Table 1.

[0135] Table 1 Compressive strength (MPa) of various grouts at different ages

[0136] serial number Sample Name 3D compressive strength 5d compressive strength 28-day compressive strength Slurry A Example 1 (Ternary + Auxiliary Components) 2.62 5.56 11.52 Slurry B Example 2 2.51 5.40 11.26 Slurry C Example 3 2.58 4.85 10.35 Comparison of slurry D1 Comparative Example 1 (Binary: Hydroxyapatite + Nanocrystal Seeds) 2.56 5.12 10.85 Comparison of slurry D2 Comparative Example 2 (Binary: Sodium fluorosilicate + Nanocrystals) 2.59 5.28 11.08 Comparison of slurry D3 Comparative Example 3 (Binary: Sodium fluorosilicate + Hydroxyapatite) 2.54 5.05 10.68 Comparison of slurry D4 Comparative Example 4 (Mono-component: Sodium fluorosilicate) 2.50 4.65 9.85 Comparison of slurry D5 Comparative Example 5 (Mono-component: Hydroxyapatite) 2.52 4.45 9.55 Comparison of slurry D6 Comparative Example 6 (Unary: Nanocrystal Seeds) 2.48 4.05 9.05 Comparison of slurry D7 Comparative Example 7 (ternary, without auxiliary components) 2.53 4.95 10.52

[0137] As can be seen from the results in Table 1, there are certain differences in the mechanical properties of each embodiment and the comparative example. The 28-day compressive strength is 9.05 to 11.52 MPa, which shows an overall gradient distribution. The order is closely related to the amount of slag powder and the composition of the penetrating crystallization components.

[0138] Regarding the inorganic matrix components, slag powder, as the core cementitious component, plays a dominant role in strength due to its dosage. Example 1 (30 parts slag powder) exhibited the highest 28-day strength (11.52 MPa), followed by Example 2 (30 parts slag powder) (11.26 MPa), while Example 3 (28 parts slag powder) showed the lowest (10.35 MPa). The identical slag powder content in Examples 1 and 2 resulted in comparable mechanical properties, confirming the dominant role of slag powder dosage in strength. The slightly lower slag powder content in Example 3 led to a corresponding decrease in strength, indicating that higher slag powder content results in greater hydration product formation, better matrix density, and higher strength—a pattern entirely consistent with the fundamental hydration principles of cementitious materials.

[0139] Regarding the permeation crystallization components, the 28-day strength of the binary systems (Comparative Examples 1 to 3) ranged from 10.68 to 11.08 MPa, which was generally higher than that of the unary systems (Comparative Examples 4 to 6) (9.05 to 9.85 MPa). Among them, the binary system containing sodium fluorosilicate (Comparative Example 2, 11.08 MPa) had the highest strength, followed by the binary system without sodium fluorosilicate (Comparative Example 1, 10.85 MPa). The binary system containing sodium fluorosilicate but without nanocrystal seeds (Comparative Example 3, 10.68 MPa) had a relatively lower strength. This may be related to the effect of sodium fluorosilicate hydrolysis to generate calcium fluorosilicate, which fills the micropores and increases the density.

[0140] It is worth noting that the 28-day strength of Comparative Example 7 (ternary penetrating crystallization component, without auxiliary components) was 10.52 MPa, which is higher than that of the unary system but lower than that of some binary systems (Comparative Example 1 and Comparative Example 2). The reason for this is speculated to be that the lack of nano-SiO2 resulted in insufficient pore structure refinement, and the absence of the crystallization regulator led to an excessively rapid crystallization reaction rate and uneven accumulation of local crystallization products, which in turn introduced micro-defects into the matrix, thus restricting strength development. In contrast, the 28-day strength of Example 1 (ternary penetrating crystallization component + auxiliary components) reached 11.52 MPa, the highest among all samples. This indicates that the synergistic effect of the auxiliary components (nano-SiO2, waterproofing powder, and crystallization regulator) and the ternary penetrating crystallization component not only optimized the pore structure and regulated the crystallization sequence but also avoided the generation of local defects, thereby achieving optimal mechanical properties while ensuring self-healing function.

[0141] Overall, mechanical strength mainly comes from the hydration reaction of inorganic matrix components, while the contribution of penetrating crystallization components (whether mono-, binary, or ternary) to mechanical properties is secondary. Their core role is reflected in subsequent impermeability and self-healing properties.

[0142] (II) Testing of impermeability and self-healing properties of cracks

[0143] Each grout was cast into a frustum-shaped impermeability test specimen with a top diameter of 175 mm, a bottom diameter of 185 mm, and a height of 150 mm. After standard curing for 28 days, the impermeability performance was tested. The primary impermeability pressure was determined according to the stepwise pressurization method in GB / T 50082-2009. After the test, a through-crack was created in the middle of the specimen by applying an axial load (crack width controlled between 0.3 and 0.5 mm). The cracked specimen was then cured under standard conditions for another 28 days, and the impermeability pressure was measured again. The ratio of the secondary impermeability pressure to the primary impermeability pressure was calculated, i.e., the secondary permeability grade ratio. Six specimens were taken from each test group, and the average value was calculated. The results are shown in Table 2.

[0144] Table 2 Comparison of impermeability and self-healing properties of various grouts

[0145] serial number Sample Name Primary seepage resistance pressure (MPa) Secondary seepage pressure (MPa) Secondary permeability level ratio Slurry A Example 1 (Ternary + Auxiliary Components) 1.35 2.20 1.63 Slurry B Example 2 1.28 2.02 1.58 Slurry C Example 3 1.31 2.11 1.61 Comparison of slurry D1 Comparative Example 1 (Binary: Hydroxyapatite + Nanocrystal Seeds) 1.27 1.62 1.28 Comparison of slurry D2 Comparative Example 2 (Binary: Sodium fluorosilicate + Nanocrystals) 1.29 1.69 1.31 Comparison of slurry D3 Comparative Example 3 (Binary: Sodium fluorosilicate + Hydroxyapatite) 1.26 1.72 1.36 Comparison of slurry D4 Comparative Example 4 (Mono-component: Sodium fluorosilicate) 1.22 1.56 1.28 Comparison of slurry D5 Comparative Example 5 (Mono-component: Hydroxyapatite) 1.20 1.47 1.23 Comparison of slurry D6 Comparative Example 6 (Unary: Nanocrystal Seeds) 1.18 1.39 1.18 Comparison of slurry D7 Comparative Example 7 (ternary, without auxiliary components) 1.24 1.90 1.53

[0146] The results in Table 2 show that:

[0147] Regarding primary seepage resistance pressure, the primary seepage resistance pressure of Examples 1 to 3 was 1.28–1.35 MPa, while that of the control slurry was 1.18–1.29 MPa, with no significant difference. This indicates that the primary seepage resistance performance mainly stems from the density of the inorganic matrix hydration products and the hydrophobic network formed by the waterproofing powder.

[0148] Regarding the secondary permeability grade ratio (the rate of recovery of anti-seepage pressure after fracture repair), Examples 1 to 3 of the present invention exhibit significant advantages. The secondary permeability grade ratio of Example 1 reaches 1.63, Example 2 reaches 1.58, and Example 3 reaches 1.61, all of which are much higher than those of the comparative examples.

[0149] The synergistic effect of the three permeation crystallization components has been fully verified:

[0150] Under the premise that the total proportion of the permeation crystallization components is completely consistent, the secondary permeation grade ratio of the comparative slurry D1 (binary: hydroxyapatite + nanocrystal seed) is 1.28, that of the comparative slurry D2 (binary: sodium fluorosilicate + nanocrystal seed) is 1.31, and that of the comparative slurry D3 (binary: sodium fluorosilicate + hydroxyapatite) is 1.36. All three are significantly lower than the 1.63 in Example 1. The secondary permeation grade ratios of the comparative slurries D4 (mono: sodium fluorosilicate), D5 (mono: hydroxyapatite), and D6 (mono: nanocrystal seed) are 1.28, 1.23, and 1.18, respectively, further decreasing to 1.18–1.28. Among them, sodium fluorosilicate alone has the best effect (1.28), followed by hydroxyapatite (1.23), and nanocrystal seed has the weakest effect (1.18), which is completely consistent with the order of component contribution reflected in the above binary system.

[0151] Data shows that, under the premise of completely consistent total proportions of permeable crystallizing components, the secondary permeability ratio is 1.18–1.28 when containing one component, 1.28–1.36 when containing two components, and reaches 1.63 when containing three components. Compared to the optimal value of a single component (sodium fluorosilicate 1.28), the optimal value of the binary combination (1.36 for D3) is improved by approximately 6.3%; compared to the optimal value of the binary combination, the ternary combination (Example 1) is improved by approximately 19.9%. Comparing the weakest mono-component combination (nano-seed crystals 1.18) with the strongest mono-component combination (sodium fluorosilicate 1.28), the difference is 8.5%; while the ternary combination improves by 27.3% compared to the weakest binary combination (1.28 for D1). This significant leap in improvement fully verifies that sodium fluorosilicate, hydroxyapatite, and nano-CSH seed crystals have a significant synergistic effect in improving the impermeability of solidified soil. The inventors believe the reason may be that the calcium fluorosilicate crystals formed by the hydrolysis of sodium fluorosilicate construct an initial sealing layer rich in Ca-F-Si active sites on the crack surface. The surface charge and lattice spacing of this layer precisely match the geometry of PO4³⁻ released from hydroxyapatite and its pre-nucleated clusters, inducing calcium phosphate to grow epitaxially along the sealing layer to form a dense composite shell. Meanwhile, the crystal mismatch between nano-CSH seeds and calcium fluorosilicate and calcium phosphate is less than 6%, allowing them to preferentially embed at the two-phase grain boundaries as "lattice bridges," reducing the heterogeneous nucleation energy barrier of the CSH gel by about 40%, and promoting the gel phase to fill the gaps between crystalline particles in a nano-overlapping manner. The cascading sequence of the three in crystallization kinetics is precisely coupled with the slow-release diffusion curve of Ca²⁺ in the high-calcium, high-sulfate environment of the phosphogypsum-filled cracks, avoiding the loose or porous defects of the sealing layer caused by crystallization rate mismatch, thereby achieving a synergistic improvement in impermeability.

[0152] The auxiliary components make a significant contribution to the overall performance: the secondary permeability grade ratio of the comparative slurry D7 (without nano-SiO2, waterproofing powder, and crystallization regulator) is 1.53, which is higher than that of Comparative Examples 1 to 3 containing only two components, but significantly lower than that of Example 1 (1.63). The absence of nano-SiO2 leads to insufficient pore structure refinement, the absence of waterproofing powder results in a decrease in initial impermeability, and the absence of crystallization regulator leads to an excessively rapid crystallization reaction rate and poor timing control, ultimately affecting the density and long-term durability of the crack repair. This demonstrates the indispensable synergy between the auxiliary components and the penetrating crystallizing components.

Claims

1. A highly active self-healing and impermeable phosphogypsum filling and curing agent, characterized in that, It consists of the following components in the following mass proportions: 100 parts inorganic matrix component and 3 to 7 parts functional modification component; The inorganic matrix component comprises the following components in the indicated mass proportions: Pre-treated calcium carbide slag powder 1-3 parts, 4-6 parts limestone powder 12-17 parts steel slag 15-25 parts of silicate cement clinker powder 20-30 parts of slag powder 3-8 parts silica fume 10-20 parts of lithium slag powder; The functional modification component comprises the following components in the following mass proportions: Modified lignin sulfonate powder, 0.4–0.6 parts. Sodium carboxymethyl cellulose powder, 0.1–0.3 parts. 4-5 parts of gypsum penetrating crystallization self-healing powder; The gypsum penetrating crystallization self-healing powder contains a penetrating crystallization component, which is composed of sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals in a mass ratio of 1.2-2.5: 0.8-2.0: 0.4-1.

0. The gypsum penetrating crystallization self-healing powder is composed of the following components in the indicated mass proportions: 2.5-5 parts penetrating crystallization component, 0.2-0.5 parts surface vapor-precipitated waterproof powder, 0.2-0.8 parts nano silica, and 0.04-0.25 parts auxiliary crystal growth regulating component. The auxiliary crystal growth regulating component is composed of sodium citrate and sodium gluconate in a mass ratio of 1:0.8 to 1.

4. The waterproof powder deposited on the surface vapor phase is an organosilicon alkyl hydrophobic powder.

2. The highly active self-healing and impermeable phosphogypsum filling and curing agent according to claim 1, characterized in that, The slag powder satisfies the following microstructure indices: slag quality coefficient ≥ 1.4, and based on² 9 The microstructure characterization of Si by nuclear magnetic resonance showed that the total relative content of the low-polymerization degree active structure Q1+Q2 in the slag glass was ≥80%.

3. The highly active self-healing and impermeable phosphogypsum filling and curing agent according to claim 1, characterized in that, The modified lignin sulfonate powder is prepared by sulfonation modification of calcium lignin sulfonate or sodium lignin sulfonate.

4. The preparation method of the highly active self-healing and impermeable phosphogypsum filling and curing agent according to any one of claims 1 to 3, characterized in that, Includes the following steps: A. Weigh each raw material of the inorganic matrix component and the functional modification component according to the formula; B. Add the pretreated carbide slag powder, limestone powder, steel slag, silicate cement clinker powder, slag powder, silica fume, and lithium slag powder from the inorganic matrix components into a dry powder mixer and stir at a speed of 500-800 r / min for 3-5 min to obtain inorganic mixed powder. C. Add the modified lignin sulfonate powder, sodium carboxymethyl cellulose powder, and gypsum penetrating crystallization self-healing powder from the functional modification components to the inorganic mixed powder obtained in step B, and continue stirring at a speed of 800-1000 r / min for 5-8 min until all components are mixed evenly and there is no segregation, to obtain a highly active self-healing anti-permeability phosphogypsum filling and curing agent.

5. The preparation method according to claim 4, characterized in that, The gypsum penetrating crystallization self-repairing powder described in step C is prepared as follows: Sodium fluorosilicate, hydroxyapatite, and nano-hydrated calcium silicate seed crystals are weighed according to the specified ratio, and then added together with nano-silica, surface vapor-precipitated waterproof powder, and auxiliary crystal growth regulating components into a mixer. The mixture is stirred at a speed of 1000-1500 r / min for 3-5 min to obtain the gypsum penetrating crystallization self-repairing powder.

6. The application of the high-activity self-healing and impermeable phosphogypsum filling and curing agent according to any one of claims 1 to 3 in underground mine filling, backfilling of water-bearing goaf areas, filling of water-bearing roadways and damp strata.

7. The application according to claim 6, characterized in that, Includes the following steps: S1. Pretreatment of dihydrate phosphogypsum: Add 0.5% to 1% of its own weight of quicklime to dihydrate phosphogypsum, mix thoroughly and uniformly, and then let it stand at room temperature in a sealed environment for 20 to 30 hours to obtain pretreated phosphogypsum. S2. Weigh the high-activity self-healing anti-seepage phosphogypsum filling and curing agent, the pretreated phosphogypsum and water according to a mass ratio of 1:5~7:12~16; S3. Add the highly active self-healing and impermeable phosphogypsum filling and curing agent and the pretreated phosphogypsum into the mixer and dry mix for 30-60 seconds. S4. Add clean water and mix for 3-5 minutes at a speed of 60-100 r / min until the slurry is uniform, free of agglomerates and lumps, and has stable fluidity to obtain the filling slurry.

Citation Information

Patent Citations

  • Exciting agent for mine filling material and preparation method thereof

    CN113060961A

  • Low-alkalinity and early-strength ardealite filling curing material and preparation method thereof

    CN119751012A

  • Phosphogypsum-based high-strength impervious filling material and preparation process thereof

    CN120682009A

  • Phosphogypsum-based soil stabilizer, preparation method, solidified sample and preparation method of solidified sample

    CN113716927A

  • Water-based permeable inorganic nano waterproof material and preparation method thereof

    CN114988746A